Odpowiedź:
[tex]\huge\boxed{IV.\ \left(\dfrac{1}{3}\right)^{22}\cdot9^{22}=3^{22}}[/tex]
Szczegółowe wyjaśnienie:
Potrzebne wzory:
[tex]a^n\cdot a^m=a^{n+m}\\\\\left(a^n\right)^m=a^{nm}\\\\\left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}\\\\(a\cdot b)^n=a^n\cdot b^n[/tex]
=====================================
[tex]I.\\3^8\cdot3^{12}=3^{8+12}=3^{20}\\\\II.\\\left(3^7\right)^3=3^{7\cdot3}=3^{21}\\\\III.\\\dfrac{6^{10}}{2^{10}}=\left(\dfrac{6}{2}\right)^{10}=3^{10}\\\\IV.\\\left(\dfrac{1}{3}\right)^{22}\cdot9^{22}=\left(\dfrac{1}{3}\cdot9\right)^{22}=3^{22}[/tex]
======================================
Wkażdym podpunkcie mamy te same podstawy równe 3. Liczba 3 > 1, stąd im większy wykładnik, tym większy wynik.
Zatem:
[tex]3^{10}<3^{20}<3^{21}<3^{22}[/tex]